1975
DOI: 10.1192/bjp.127.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Aspects of Hypertension

Abstract: The physiological response to stress falls mainly on the cardiovascular system, adrenergic stimulation resulting in peripheral vasoconstriction and an increase in systemic blood pressure. The analogous effects that occur in anxiety-provoking situations immediately suggest an association, whether causal or effectual, between raised blood pressure and anxiety. It has also been suggested that hypertensive individuals exhibit more aggressive traits than others and that these may be hidden or suppressed, becoming m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
2

Year Published

1980
1980
2005
2005

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 15 publications
4
14
0
2
Order By: Relevance
“…This dimension focuses on feelings of personal inadequacy and inferi ority, particularly in comparison to other persons (6). Our data confirm previous findings using a different version of SCL (4) published in literature (13,20).…”
Section: Resultssupporting
confidence: 83%
“…This dimension focuses on feelings of personal inadequacy and inferi ority, particularly in comparison to other persons (6). Our data confirm previous findings using a different version of SCL (4) published in literature (13,20).…”
Section: Resultssupporting
confidence: 83%
“…The widespread use of prescribed hypnotic medication and non-prescription remedies is an indirect reflect of this high frequency of sleep complaints and its related morbidity (Mellinger et al 1985;Wheatley et al 1975). In this context, benzodiazepines, including flunitrazepam, flurazepam, lormetazepam, temazepam and triazolam are among the most commonly prescribed drug treatments for insomnia (Gold et al 1995;Nowell et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Davies' finding that recently diagnosed hypertensives score sig nificantly lower for neuroticism than normo tensives has been confirmed by most later studies [12][13][14][15], However, varying results have been obtained for hypertensives who are aware of having this illness. While some investigators did not find any difference be tween 'aware' hypertensives and normoten sives in the level of neuroticism [5,14,15], others reported that the 'aware' hyperten sives tended to score higher than the controls for neuroticism [11][12][13]16].…”
Section: Introductionmentioning
confidence: 82%